Penggunaan Media Magic Box untuk Meningkatkan Hasil Belajar IPA pada Siswa Kelas V MIN 1 Bangkalan - Addely Damayanti Noer; Siti Maisaroh; Qurrotul Aini; Agung Setyawan (Journal on Education, 2023)
This research was conducted with the aim to: 1) To improve student learning outcomes in science learning by applying magic box learning media, 2) To develop students' understanding in science learning. The method used is Classroom Action Research (PTK) where each cycle goes through 4 stages, namely: (1) planning, (2) action, (3) observation, (4) reflection. The results showed that learning by using magic box media had a positive impact on increasing the achievement of students' learning achievement as shown by the increasing percentage of student learning completeness in cycle 2 which reached 85.71%.